Foods Inducing Typical Gastroesophageal Reflux Disease Symptoms in Korea - Choe, Jung Wan (J Neurogastroenterol Motil, 2017)
BACKGROUND/AIMS: Several specific foods are known to precipitate gastroesophageal reflux disease (GERD) symptoms and GERD patients are usually advised to avoid such foods. However, foods consumed daily are quite variable according to regions, cultures, etc. This study was done to elucidate the food items which induce typical GERD symptoms in Korean patients. METHODS: One hundred and twenty-six Korean patients with weekly typical GERD symptoms were asked to mark all food items that induced typical GERD symptoms from a list containing 152 typical foods consumed daily in Korea. All patients underwent upper gastrointestinal endoscopy followed by 24-hour ambulatory esophageal pH monitoring. The definition of “GERD” was if either of the 2 studies revealed evidence of GERD, and “possible GERD” if both studies were negative. RESULTS: One hundred and twenty-six cases (51 GERD and 75 possible GERD) were enrolled. In 19 (37.3%) of 51 GERD cases and in 17 (22.7%) of 75 possible GERD cases, foods inducing typical GERD symptoms were identified. In the GERD group (n = 19), frequent symptom-inducers were hot spicy stews, rice cakes, ramen noodles, fried foods, and topokki. In the possible GERD group (n = 17), frequent symptom-inducers were hot spicy stews, fried foods, doughnuts, breads, ramen noodles, coffee, pizza, topokki, rice cakes, champon noodles, and hotdogs. CONCLUSIONS: In one-third of GERD patients, foods inducing typical symptoms were identified. Hot spicy stews, rice cakes, ramen noodles, fried foods, and topokki were the foods frequently inducing typical symptoms in Korea. The list of foods frequently inducing typical GERD symptoms needs to be modified based on their own local experiences.